Marginal Utilities and Marginal Costs of Having Children - Mihályi, Péter (Public Finance Quarterly, 2019)
When families make decisions about having a child ex ante, they calculate with steeply decreasing marginal utilities. In other words, the 1st baby brings a huge amount of pleasure (utility), while the 2nd and further babies bring less and less utilities. Historically, it hasn’t always been this way: in poor societies, the main motive for having children was that children were able to work from a young age. Therefore, marginal utility decreased only slightly, to the point around the average utility. The social utility of having children only has a slight influence on families; however, every new child’s social utility is almost the same. This explains politicians’ intentions to encourage families to have more children. The final conclusion is that within the factors taken into consideration in the study, there is no equilibrium, and the observable trends will not result in a social optimum. Decreasing population and the aging of the society cannot be eliminated or significantly alleviated on national level, no matter the amount of money the government is willing to spend to take over some of the costs parents bear to have children.